7
$\begingroup$

How to prove this inequality: $$(x_1y_1+x_2y_2+ \cdots + x_ny_n)^2 - (x_1^2y_1^2+x_2^2y_2^2+\cdots+x_n^2y_n^2)\leq 1-\frac{1}{n},$$ where $x_i,y_i \geq 0,i=1,2,\ldots,n$, and $x_1^2+x_2^2+\cdots+x_n^2=y_1^2+y_2^2+\cdots+y_n^2=1$?

Clearly, the equality is reached when $x_i=y_i=\frac{1}{n},i=1,2,\ldots,n$.

$\endgroup$
  • $\begingroup$ I think Titu's Lemma might help. $\endgroup$ – Prasun Biswas Apr 13 '15 at 11:43
8
$\begingroup$

By$\let\leq\leqslant$ Cauchy-Schwarz, $$\begin{align*}(x_1y_1+\cdots+x_ny_n)^2&\leq(x_1^2y_1^2+\cdots+x_n^2y_n^2)\cdot(1^2+\cdots+1^2)\\&=n(x_1^2y_1^2+\cdots+x_n^2y_n^2)\end{align*}\tag A$$ and $$(x_1y_1+\cdots+x_ny_n)^2\leq(x_1^2+\cdots+x_n^2)(y_1^2+\cdots+y_n^2).\tag B$$

$\frac1n\cdot({\rm A})+(1-\frac1n)\cdot({\rm B})$ gives your inequality:

$$\begin{align*}(x_1y_1+\cdots+x_ny_n)^2&\leq(x_1^2y_1^2+\cdots+x_n^2y_n^2)+\left(1-\frac1n\right)(x_1^2+\cdots+x_n^2)(y_1^2+\cdots+y_n^2)\\&=x_1^2y_1^2+\cdots+x_n^2y_n^2+1-\frac1n\end{align*}$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.